Patient specific stem cells - Lamba, Deepak Ashok; Taylor and Francis (Boca Raton, FL : CRC Press, an imprint of Taylor and Francis, 2017)
One of the biggest challenges faced in medical research had been to create accurate and relevant models of human disease. A number of good animal models have been developed to understand the pathophysiology. However, not all of them reflect the human disorder, a classic case being Usher's syndrome where the mutant mice do not have the same visual and auditory defects that patients face. There are others which have been even more difficult to model due to the multi-factorial nature of the condition and due to lack of discovery of a single causative gene such as age-related macular degeneration or Alzheimer's syndrome. Thus a more relevant and accurate system will allow us to make better predictions on relevant therapeutic approaches. The discovery of human pluripotent stem cells in 1998 followed by the technological advances to reprogram somatic cells to pluripotent-stem cell-like cells in 2006 has completely revolutionized the way we can now think about modelling human development and disease. This now coupled with genome editing technologies such as TALENS and CRISPRs have now set us up to develop in vitro models both 2D as well as 3D organoids, which can more precisely reflect the disease in the patients. These combinatorial technologies are already providing us with better tools and therapeutics in drug discovery or gene therapy. This book summarizes both the technological advances in the field of generation of patient specific lines as well as various gene editing approaches followed by its applicability in various systems. The book will serve as a reference for the current state of the field as it: -Provides a comprehensive overview of the status of the field of patients derived induced pluripotent stem cells.-Describes the use of cardiac cells as a main featured component within the book.-Examines drug toxicity analysis as a working example throughout the book.
Preface -- About the Editor -- Contributors -- 1. Human-Induced Pluripotent Stem Cells: Derivation / Uthra Rajamani, Lindsay Lenaeus, Loren Ornelas, and Dhruv Sareen -- 2. Human-Induced Pluripotent Stem Cells: Banking and Characterization / Uthra Rajamani, Lindsay Lenaeus, Loren Ornelas, and Dhruv Sareen -- 3. Genetic and Epigenetic Considerations in iPSC Technology / Yoshiaki Tanaka and In-Hyun Park -- 4. CRISPR-Based Genome Engineering in Human Stem Cells / Thelma Garcia and Deepak A. Lamba -- 5. Stem Cells for Parkinson's Disease / Deepak A. Lamba -- 6. Huntington's Disease and Stem Cells / Karen Ring, Robert O'Brien, Ningzhe Zhang, and Lisa M. Ellerby -- 7. Applications of Pluripotent Stem Cells in the Therapy and Modeling of Diabetes and Metabolic Diseases / Suranjit Mukherjee and Shuibing Chen -- 8. Role of iPSCs in Disease Modeling: Gaucher Disease and Related Disorders / Daniel K. Borger, Elma Aflaki, and Ellen Sidransky -- 9. Role of Induced Pluripotent Stem Cells in Urological Disease Modeling and Repair / Mohammad Moad, Emma L. Curry, Craig N. Robson, and Rakesh Heer -- 10. Induced Pluripotent Stem Cells: A Research Tool and a Potential Therapy for RPE-Associated Blinding Eye Diseases / Ruchi Sharma, Balendu Shekhar Jha, and Kapil Bharti -- 11. Modeling Neuroretinal Development and Disease in Stem Cells / Deepak A. Lamba -- Index.
Keywords: Pluripotent Stem Cells; SCIENCE / Biotechnology